2018
DOI: 10.1186/s40479-018-0087-7
|View full text |Cite
|
Sign up to set email alerts
|

Negative urgency partially accounts for the relationship between major depressive disorder and marijuana problems

Abstract: BackgroundTo goal of this study was to better understand mechanisms underlying associations between Major Depressive Disorder (MDD) and marijuana use and problems. Specifically, it was hypothesized that negative urgency (NU), the tendency to act rashly while experiencing negative mood states, would uniquely (compared to other impulsivity traits: positive urgency, sensation seeking, premeditation, and perseverance) account for the relationship between MDD and marijuana use and problems.MethodsData were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 68 publications
1
14
0
Order By: Relevance
“…Thus, it is possible that individuals with more severe insomnia were using marijuana to cope with the associated negative mood, and this coping motivation led to worse marijuana‐related problems. Second, given research suggesting associations between negative mood, negative urgency (tendency to engage in rash action due to negative affect) and marijuana problems (Gunn, Jackson, Borsari, & Metrik, ), it is possible that negative mood as a result of more severe insomnia may have predisposed individuals to act more impulsively, leading to more consequences related to their marijuana use. Finally, neuroimaging findings have linked both insomnia and marijuana use with reductions in prefrontal activity (Babson & Bonn‐Miller, ; Drummond, Smith, Orff, Chengazi, & Perlis, ), which has been shown to be associated with decreased top‐down control of the amygdala, disrupted mood regulation and persistence of negative affect (for a review see Palagini, Bastien, Marazziti, Ellis, & Riemann, ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is possible that individuals with more severe insomnia were using marijuana to cope with the associated negative mood, and this coping motivation led to worse marijuana‐related problems. Second, given research suggesting associations between negative mood, negative urgency (tendency to engage in rash action due to negative affect) and marijuana problems (Gunn, Jackson, Borsari, & Metrik, ), it is possible that negative mood as a result of more severe insomnia may have predisposed individuals to act more impulsively, leading to more consequences related to their marijuana use. Finally, neuroimaging findings have linked both insomnia and marijuana use with reductions in prefrontal activity (Babson & Bonn‐Miller, ; Drummond, Smith, Orff, Chengazi, & Perlis, ), which has been shown to be associated with decreased top‐down control of the amygdala, disrupted mood regulation and persistence of negative affect (for a review see Palagini, Bastien, Marazziti, Ellis, & Riemann, ).…”
Section: Discussionmentioning
confidence: 99%
“…To test study aims, and considering the cross-sectional nature of the data, we employed a path analysis to examine the atemporal mediation ( Winer et al, 2016 ) of DT in the associations between self-control variables (i.e., impulsivity-like traits, self-regulation, and emotion regulation strategies) and SNSs outcomes (i.e., time spent using SNSs and problematic use). Prior research suggested that including all five UPPS-P facets in one model might create a suppression effect because some dimensions are highly intercorrelated ( Gunn et al, 2018 , Gunn and Smith, 2010 ). Therefore, before deciding which UPPS-P dimensions to include in the mediation model, we estimated the bivariate Pearson correlations between each UPPS-P facet, DT (i.e., the mediator) and SNS outcomes.…”
Section: Methodsmentioning
confidence: 99%
“…Impulsivity is not a unitary construct (Adams et al, 2012;Maraz et al, 2016), but it is a multifaceted (Evren & Bozkurt, 2017;Maccalum et al, 2007;Netto et al, 2016), multidimensional (Adams et al, 2012;Maccalum et al, 2007;Magid et al, 2007;Ramakrishnan et al, 2019), complex (Magid et al, 2007), heterogeneous (Dick et al, 2010) construct. Impulsivity is characterized by rapid, unpredictable, unplanned, spontaneous, rashly and sudden reactions to stimuli (Adams et al, 2012;Chase et al, 2017;Dick et al, 2010;Maccalum et al, 2007;Pérez Fuentes et al, 2016;Ramakrishnan et al, 2019), rapid decision-making and action (Magid et al, 2007;Patton et al, 1995), before complete processing of information, without considering all the information available (Maccalum et al, 2007;Molero Jurado et al, 2020;Pérez Fuentes et al, 2016), without adequate forethought, deliberation, premeditation or planning (Adams et al, 2012;Charnigo et al, 2013;Chase et al, 2017;Daurio et al, 2018;Dick et al, 2010;Gunn et al, 2018;Harden & Tucker-Drob, 2011;Johansen, 2014;Lynam, n.d.;Maccalum et al, 2007;Magid et al, 2007;Merchán-Clavellino et al, 2020;Molero Jurado et al, 2020;Patton et al, 1995;Ramakrishnan et al, 2019;Reas et al, 2016;…”
Section: Definitions Of Impulsivitymentioning
confidence: 99%
“…the tendency to experience strong impulses and act rashly under conditions of negative mood states, and positive urgency, i.e. the tendency towards rash actions in response to positive mood (Adams et al, 2012;Chase et al, 2017;Daurio et al, 2018;Dick et al, 2010;Gunn et al, 2018;Lynam, n.d.;Ramakrishnan et al, 2019;Reas et al, 2016;Wan et al, 2020;Whiteside & Lynam, 2001;Zhao et al, 2017), decreased sensitivity to negative consequences of behavior and decreased sensitivity to punishment (Cross et al, 2011;Maccalum et al, 2007;Merchán-Clavellino et al, 2020), decreased sensitivity to non-reward (Wan et al, 2020), preference for and sensitivity to immediate smaller reward (Chase et al, 2017;Cheng, 2020;Cross et al, 2011;Maccalum et al, 2007;Merchán-Clavellino et al, 2020;Molero Jurado et al, 2020;Pérez Fuentes et al, 2016;Wan et al, 2020), deficits in self-control, a repeated failure of self-discipline and self-regulation (Cross et al, 2011;Maccalum et al, 2007;Ramakrishnan et al, 2019;Zuckerman, 2014), lack of perseverance (Adams et al, 2012;Chase et al, 2017;Daurio et al, 2018;Dick et al, 2010;Gunn et al, 2018;Lynam, n.d.;Merchán-Clavellino et al, 2020;Ramakrishnan et al, 2019;Reas et al, 2016;Wan et al, 2020;…”
Section: Definitions Of Impulsivitymentioning
confidence: 99%
See 1 more Smart Citation